2021
DOI: 10.1371/journal.pone.0247365
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effect of hyperthermic massage and mechanical squeezing in the patients with mild and severe meibomian gland dysfunction: An interventional case series

Abstract: Background Meibomian glands exist beneath the palpebral conjunctiva; thus, it is invisible to the naked eye without infrared imaging. This study used meibography to group patients with meibomian gland dysfunction (MGD) and assessed the effects of hyperthermic massage and mechanical squeezing in both groups. Materials and methods Patients with MGD were divided into two groups, according to the degree of meibomian gland loss: group 1, in which the sum of eyelid scores ranged from 0 to 4 (mild to moderate gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…MGD can reduce TFLLT and alter its distribution, consequently leading to dry eye symptoms, ocular irritation, and many other symptoms. Warm compression, eyelid hygiene, and mechanical squeezing are usually recommended for MGD treatment [ 5 , 18 ]. Multiple studies have reported long-term effectiveness of warm lid compression and mechanical expression in treating MGD [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MGD can reduce TFLLT and alter its distribution, consequently leading to dry eye symptoms, ocular irritation, and many other symptoms. Warm compression, eyelid hygiene, and mechanical squeezing are usually recommended for MGD treatment [ 5 , 18 ]. Multiple studies have reported long-term effectiveness of warm lid compression and mechanical expression in treating MGD [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Warm compression, eyelid hygiene, and mechanical squeezing are usually recommended for MGD treatment [ 5 , 18 ]. Multiple studies have reported long-term effectiveness of warm lid compression and mechanical expression in treating MGD [ 18 , 19 ]. However, immediate effects of such treatments and comparisons of those effects between the normal group and the MGD group have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Meibomian gland expression is a treatment for DED by promoting the drainage of obstruent meibomian secretion, usually with the help of glass rods, chalazion clamps, strabismus hooks, and other tools. [7][8][9] It is generally recommended to carry out after a hot compress and squeeze the upper and lower meibomian glands. It has been used to treat DED for at least 90 years.…”
Section: Introductionmentioning
confidence: 99%
“…The management of MGD involves a comprehensive approach, which includes eyelid hygiene, warm compresses, and medications [5]. One such medication is minocycline, a tetracycline antibiotic with anti-inflammatory properties, which has been used to treat various ocular surface diseases, including MGD [6].…”
Section: Introductionmentioning
confidence: 99%